Aerodynamic and acoustic characteristics of voice in children with down syndrome-A systematic review. (June 2020) - Krishnamurthy, Rahul; Ramani, Sai Aishwarya
Abstract: Purpose: The anatomical, physiological, and phenotypic characteristics of children with Down Syndrome results in deviated acoustic and aerodynamic measures in their voice. These deviant vocal presentations may negatively affect the quality of life of children with Down syndrome. The present study aimed to systematically review the available literature on acoustic and aerodynamic voice characteristics of children with Down syndrome. Method: A systematic review of studies on acoustic and aerodynamic measures of voice in children with Down Syndrome (using PubMed/MEDLINE, CINAHL, Scopus, ProQuest, Cochrane, Ovid, Science Direct) was carried out. Keywords based on Population–Investigation–Outcome were used to develop search strings. Two authors screened titles and abstracts independently, and appropriate studies were analyzed in detail for data extraction. Results: Out of the 1432 studies, two studies met the inclusion criteria. Different acoustic and aerodynamic measures were employed, such as fundamental frequency, intensity, phonation time, jitter, shimmer and ESGP, MAFR, and LAR. Conclusion: Overall, there was a lack of standardized criteria for the evaluation of acoustic and aerodynamic characteristics in the Down syndrome population. Acoustically, there was no significant difference between children with DS and typically developing children. However, aerodynamic studies suggest that there is a significant impairment of glottal valving in children with Down syndrome.